Energy-efficient prefabricated monolithic foundation for small and medium-rise buildings - Ospanova, Жумабике; Esmagambetov, Ержан (Рroblems of engineering and professional education, 2023)
The share of the construction of low-rise buildings in the total volume of the market is increasing every year. Low-rise houses attract a growing number of investors and customers. The analysis of this segment of the construction market shows that the demand for a low-rise apartment buildings and individual houses. Kazakhstanis start to appreciate the opportunity to live in ecologically clean areas not less than those in European or American cities.